PENDEKATAN KONSEP QUADRUPLE HELIX DALAM MENINGKATKAN PENDAPATAN, NILAI TAMBAH DAN KEBERLANJUTAN USAHA KERUPUK IKAN BANDENG (Studi Kasus di Pucangro Lamongan) - Suyoto Suyoto; Faisol Mas’ud (Universitas Galuh, 2022)
Milkfish is the main aquaculture commodity in Lamongan Regency besides vannamei shrimp. But in reality milkfish meat has not been used optimally in the fish cracker processing business. This study aims to analyze the added value and income as well as to find a sustainable strategy for processing milkfish crackers using the quadruple Helix concept approach. The research method is descriptive quantitative with a case study approach. the sampling is done by purposive sampling. Analysis of the data by calculating profit or net income, added value using the Hayami method and recommendations for sustainability with SWOT analysis. The final result shows that the milkfish cracker processing business earns a profit of Rp. 8,722,917 per twenty-six times the production process for one month, with an added value of Rp. 63,540/kg of raw materials. From the SWOT analysis, the Aggressive Strategy is obtained. The strategy is to increase the production of milkfish crackers by developing the business by increasing the quality and quantity due to market guarantees. For business sustainability, collaboration is used in the quadruple helix concept, namely (1) Entrepreneurs play a role in increasing production, (2) Academics play a role in providing assistance to product innovation and marketing research that is more effective, (3) The government plays a role in providing counseling, training and business capital assistance, (4) The community plays a role by participating in developing this milkfish cracker processing business into a superior product for the local area and helping to promote it through online promotion media so that it is more widely known.